Participants' Engagement and Satisfaction With a Smartphone App Intended to Support Healthy Weight Gain, Diet, and Physical Activity During Pregnancy: Qualitative Study Within the HealthyMoms Trial - Sandborg, Johanna; Henriksson, Pontus; Larsen, Erica; Lindqvist, Anna-Karin; Rutberg, Stina; Söderström, Emmie; Maddison, Ralph; Löf, Marie (JMIR Publications, 2021)
BackgroundExcessive gestational weight gain (GWG) is common and associated with negative health outcomes for both mother and child. Mobile health-delivered lifestyle interventions offer the potential to mitigate excessive GWG. The effectiveness of a smartphone app (HealthyMoms) was recently evaluated in a randomized controlled trial. To explore the users' experiences of using the app, a qualitative study within the HealthyMoms trial was performed. ObjectiveThis qualitative study explored participants' engagement and satisfaction with the 6-month usage of the HealthyMoms app. MethodsA total of 19 women (mean age: 31.7, SD 4.4 years; mean BMI: 24.6, SD 3.4 kg/m2; university degree attainment: 13/19, 68%; primiparous: 11/19, 58%) who received the HealthyMoms app in a randomized controlled trial completed semistructured exit interviews. The interviews were audiorecorded and fully transcribed, coded, and analyzed using thematic analysis with an inductive approach. ResultsThematic analysis revealed a main theme and 2 subthemes. The main theme, "One could suit many: a multifunctional tool to strengthen women's health during pregnancy," and the 2 subthemes, "Factors within and beyond the app influence app engagement" and "Trust, knowledge, and awareness: aspects that can motivate healthy habits," illustrated that a trustworthy and appreciated health and pregnancy app that is easy to use can inspire a healthy lifestyle during pregnancy. The first subtheme discussed how factors within the app (eg, regular updates and feedback) were perceived to motivate both healthy habits and app engagement. Additionally, factors beyond the app were described to both motivate (eg, interest, motivation, and curiosity) and limit (eg, pregnancy-related complications, lack of time) app engagement. The second subtheme reflected important aspects, such as high trustworthiness of the app, increased knowledge, and awareness from using the app, which motivated participants to improve or maintain healthy habits during pregnancy. ConclusionsThe HealthyMoms app was considered a valuable and trustworthy tool to mitigate excessive GWG, with useful features and relevant information to initiate and maintain healthy habits during pregnancy. Trial RegistrationClinicalTrials.gov NCT03298555; https://clinicaltrials.gov/ct2/show/NCT03298555 International Registered Report Identifier (IRRID)RR2-10.2196/13011